University of 21st century: contours in the context of modernity crisis - M. V. Tlostanova (Moscow Polytechnic University, 2022)
In today's world there are three main types of reaction to the systemic crisis of modernity, including its knowledge and educational spheres - rewesternization, dewesternization, and decoloniality. The article considers how these models are implemented in the main tendenciesof university development as an institution. It either bends more and more in the direction ofthe "Davos culture" and ultimate corporativization, or exists within the frame of the multi-polar world and polycentric capitalism ideology. Finally, the third option is a radical delinking from the previous principles of the university as one of the two main modernity institutes for the production and dissemination of a particular normative knowledge. The author strives to define where does the Russian university stand in this scheme. Specific attention is also paid tothe humanities in contemporary university and their prospects for the 21st century.